2006
DOI: 10.1902/jop.2006.050360
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interdental Cleaning Methods: A Randomized Controlled Trial

Abstract: This trial demonstrated that patients were able to improve clinical periodontal outcomes by interdental cleaning, particularly with interdental brushes, even before thorough root surface debridement was undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 26 publications
5
60
1
7
Order By: Relevance
“…[23] and Jackson et al . [24] have proved that by use of interdental cleaning aids, periodontal patients are able to improve clinical outcomes and reduce clinical signs of disease and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[23] and Jackson et al . [24] have proved that by use of interdental cleaning aids, periodontal patients are able to improve clinical outcomes and reduce clinical signs of disease and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ara yüzlerin etkin bir şekilde temizlenememesi, sondalamada kanama ve sondalama derinliklerinde artış ile periodontal hastalığın oluşmasına zemin hazırlamaktadır. 8 Bu sebeple hekimler, bireyin ihtiyacına uygun temizleme araçları ve bu araçların kullanım teknikleri hakkında literatürdeki kanıta dayalı veriler ışığında hastalarını bilgilendirmekle yükümlüdür.…”
Section: Discussionunclassified
“…One additional study was gleaned from the reference list, for a total of 9 studies included in this systematic review. [1][2][3][4][5][6][7][8][9] Both randomized controlled clinical trails and controlled clinical trials were selected for review; however, considerable heterogeneity was observed in the 9 studies related to study design, number, gender and age of participants, and outcome variables.…”
mentioning
confidence: 99%